2020
DOI: 10.3389/fimmu.2020.571321
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometry-Based Protocols for the Analysis of Human Plasma Cell Differentiation

Abstract: Humoral immunity is established after differentiation of antigen-specific B cells into plasma cells (PCs) that produce antibodies of relevant specificities. Defects in the development, activation, or differentiation of B cells severely compromises the immune response. Primary immunodeficiencies are often characterized by hypogammaglobulinemia and the inability to mount effective antigen-specific antibody responses, resulting in increased susceptibility to infections. After IgA deficiency, which is most often a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Pathogenic loss-of-function or gain-of-function heterozygous variants have been reported to be associated with CVID. However, their functional relevance for susceptibility to infection and response to vaccination remains to be clarified ( 8 ). Unfortunately, genetic causes of most CVID cases remain undefined, and the diagnosis is predominantly based on hypogammaglobulinemia with impairment of antibody response to vaccine or natural antigen and reduced memory B cells (MBCs) frequency.…”
Section: Susceptibility To Vaccine-preventable Infectionsmentioning
confidence: 99%
“…Pathogenic loss-of-function or gain-of-function heterozygous variants have been reported to be associated with CVID. However, their functional relevance for susceptibility to infection and response to vaccination remains to be clarified ( 8 ). Unfortunately, genetic causes of most CVID cases remain undefined, and the diagnosis is predominantly based on hypogammaglobulinemia with impairment of antibody response to vaccine or natural antigen and reduced memory B cells (MBCs) frequency.…”
Section: Susceptibility To Vaccine-preventable Infectionsmentioning
confidence: 99%
“…The mean stimulation index of camel PBML (10.43 ± 0.92) was significantly higher (p < 0.05) than those of goats (5.03 ± 0.90), sheep (5.62 ± 0.62), and cows (5.53 ± 0.78), in the presence of PWM. Although it cannot be determined from the present study whether a specific subpopulation of lymphocytes from camels is stimulated by PWM, it has been demonstrated in cows [53], humans [54], and mice [55] that PWM is capable of stimulating both T and B cells. Indeed, when T-cells were removed from lymphocytes by treating the cells with anti-CD4 antibody and depleted by a fluorescent activated cell sorter, there was a lowering of PWM-induced activity [53].…”
Section: Mitogenesismentioning
confidence: 71%
“…Indeed, when T-cells were removed from lymphocytes by treating the cells with anti-CD4 antibody and depleted by a fluorescent activated cell sorter, there was a lowering of PWM-induced activity [53]. Other studies have demonstrated that the number of T-cells presented in the culture stimulated with PWM increased the number of intracytoplasmic immunoglobulins in murine and human B-lymphocytes [54,55].…”
Section: Mitogenesismentioning
confidence: 99%
“…Both ceritinib and entrectinib inhibited mature B cell populations in multiple experiments (summarized in Figure 1 ), with ceritinib showing lower EC50 concentrations and more consistent numbers ( Figure 1 ). We then focused on live cell populations of these CD19-positive B cells and analyzed the presence of mature BLIMP1/IRF4 double-positive lymphocytes, i.e., plasma cells [ 26 , 33 ] ( Figure 2 ). We found that the majority of live CD19-positive lymphocytes in our experiments with tyrosine kinase inhibitors were BLIMP1/IRF4 double-positive (62 ± 7.7%, Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%